2011
DOI: 10.1089/jwh.2010.2042
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual Cycle Effects on Perceived Exertion and Pain During Exercise Among Sedentary Women

Abstract: Background: Increasing cardiovascular fitness through exercise participation among sedentary people is important for decreasing all-cause mortality. From an intervention perspective, identifying modifiable factors that maximize the successful initiation of exercise is of utmost importance. For women, cyclic hormonal variations can influence aspects of health and health behaviors, from smoking cessation efficacy to physiological responses to exercise. The purpose of this study was to examine the influence of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 48 publications
2
22
0
1
Order By: Relevance
“…Previous findings that reported no difference in muscle soreness following eccentric exercise between follicular and luteal phase may be confounded by the inclusion of part OC users and nonusers [22] or measurement in mid-follicular phase with rising oestrogen concentrations [20]. In support of the current findings, a previous study reports greater perception of pain and rating of perceived exertion during exercise in women during the EF phase compared with the LF or ML phase [43]. The influence of the menstrual cycle on pain perception is complicated and not clearly described [44].…”
Section: Discussionsupporting
confidence: 80%
“…Previous findings that reported no difference in muscle soreness following eccentric exercise between follicular and luteal phase may be confounded by the inclusion of part OC users and nonusers [22] or measurement in mid-follicular phase with rising oestrogen concentrations [20]. In support of the current findings, a previous study reports greater perception of pain and rating of perceived exertion during exercise in women during the EF phase compared with the LF or ML phase [43]. The influence of the menstrual cycle on pain perception is complicated and not clearly described [44].…”
Section: Discussionsupporting
confidence: 80%
“…An important observation was that the RPE at minute 30 of the MLSS ride was significantly higher in the mid‐follicular phase compared with the mid‐luteal phase of the menstrual cycle but did not differ between oral contraceptive cycle phases. Although there is minimal information about the influence of hormonal fluctuations on subjective responses to exercise, a large study (n = 117) found steeper increases in pain and RPE across an exercise bout in the early‐follicular phase compared with the late‐follicular or luteal phases in sedentary non‐hormonal contraceptives users, but not among hormonal contraceptives users . It was suggested that differences in the responses between groups may be a result of less variability in hormones across the hormonal contraceptive cycle .…”
Section: Discussionmentioning
confidence: 99%
“…Although there is minimal information about the influence of hormonal fluctuations on subjective responses to exercise, a large study (n = 117) found steeper increases in pain and RPE across an exercise bout in the early‐follicular phase compared with the late‐follicular or luteal phases in sedentary non‐hormonal contraceptives users, but not among hormonal contraceptives users . It was suggested that differences in the responses between groups may be a result of less variability in hormones across the hormonal contraceptive cycle . Because RPE may be difficult to differentiate from pain, another explanation could be that RPE values at the end of the MLSS trial may have been affected by a decreased perception of pain in the mid‐luteal phase compared with the late‐follicular phase (known as the “luteal analgesia” effect) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not evaluate study subjects during a specific phase of menstrual cycle. While the effects of menstrual cycle phase on pain sensitivity have been controversial [30], we chose not to control for this factor as 1) we anticipated that multiple subjects would be menopausal due to either posthysterectomy or other endometriosis treatment; 2) our study outcomes focused on within‐session change scores; and 3) multiple subjects would be on oral contraceptives that are known to blunt any potential cycle‐related variability in pain sensitivity [31,32].…”
Section: Methodsmentioning
confidence: 99%